KOORDINASI ANTARA KEJAKSAAN DAN APARAT PENGAWASAN INTERNAL PEMERINTAH DALAM PENANGANAN LAPORAN ATAU PENGADUAN PENYELENGGARAAN PEMERINTAH DI KOTA PONTIANAK - Indra Safwatulloh, Mochamad; Syafei, Muhammad; Saptomo, Priyo (Nestor : Tanjungpura Journal of Law, 2024)
Abstract  This research aims to describe and analyze the implementation of coordination between the Prosecutor's Office and the Government Internal Monitoring Apparatus (APIP) in handling reports or complaints about government administration, especially in Pontianak City as well as obstacles in handling and efforts to overcome these obstacles.Research is divided into two, namely normative legal research and sociological or empirical legal research. Data analysis was carried out using descriptive juridical and qualitative methods, which were carried out according to the information or data obtained when the research was carried out, then processed and applied as a tool for analysis and discussion of research results.The results of the research found that APIP will only submit the Audit Results Report and Minutes files to the Pontianak District Prosecutor's Office if there is a failure to recover state financial losses by government officials in Pontianak City. Factors inhibiting coordination between the Pontianak District Prosecutor's Office and APIP come from regulatory factors, APIP's role will be hampered by its position as a subordinate to the Regional Head as well as the minimal amount of evidence and evidence attached by the reporter as well as the limited number and ability to carry out investigative audits. Optimizing coordination between APIP and the Pontianak District Prosecutor's Office is carried out in accordance with the scope of duties and authorities held individually or jointly.  Keywords: Coordination; Complaint; Government Administrator; Report  Abstrak  Penelitian ini bertujuan menguraikan dan menganalisis pelaksanaan koordinasi antara Kejaksaan dengan APIP dalam menangani penanganan laporan atau pengaduan penyelenggaraan pemerintah, khususnya di Kota Pontianak serta hambatan dalam penanganan dan upaya mengatasi hambatan tersebut.Penelitian terbagi menjadi dua yaitu penelitian hukum normatif dan penelitian hukum sosiologis atau empiris. Analisa data dilakukan dengan metode deskriptif yuridis dan kualitatif, yang dilakukan sesuai informasi atau data yang diperoleh pada saat penelitian dilakukan, kemudian diolah dan diaplikasikan sebagai alat analisis dan pembahasan hasil penelitian.Hasil penelitian menemukan bahwa APIP baru akan menyerahkan berkas Laporan Hasil Pemeriksaan dan Berita Acara kepada Kejari Pontianak bila terjadi kegagalan pengembalian kerugian keuangan negara oleh penyelenggara pemerintah di Kota Pontianak. Faktor penghambat koordinasi antara Kejari Pontianak dan APIP berasal dari faktor regulasi, peran APIP akan terbentur dengan posisinya sebagai bawahan Kepala Daerah serta minimnya jumlah alat bukti dan barang bukti yang dilampirkan pelapor serta terbatasnya jumlah dan kemampuan dalam melakukan audit investigatif. Optimalisiasi koordinasi APIP maupun Kejari Pontianak dilakukan sesuai lingkup tugas dan kewenangan yang dimiliki masing-masing maupun secara bersama.